Reproducibility of Relaxation Times and Spin Density Calculated from Routine MR Imaging Sequences: Clinical Study of the CNS - Kjos, Bent O.; Ehman, Richard L.; Brant-Zawadzki, Michael; Kelly, William M.; Norman, David; Newton, Thomas H. (American Journal of Neuroradiology, 1985)
This study was undertaken to determine if routine clinical magnetic resonance imaging sequences using only two different repetition times (TRs) and with only two sequential spin echoes (SEs) can be used to calculate reproducible relaxation time and spin density values for normal central nervous system tissue using a 0.35 T production-model instrument. In 43 patients 650 regions of interest of 11 different anatomic sites were measured. T1 and T2 relaxation times and spin density were measured. For each anatomic location, the mean and standard deviation of these values were determined. In most solid regions of brain, the standard deviation of both T1 and T2 was 4%–8%. Relaxation times of cortical gray matter varied more, with a standard deviation of 10%, probably because of volume-averaging with adjacent cerebrospinal fluid (CSF). CSF and ocular vitreous humor were neither reproducibly nor accurately measured because of the short TR and TE settings of the imaging sequences relative to the long T1 and T2 relaxation times of these substances. Significant and reproducible differences were found between the spin densities of gray matter and white matter, as well as between different regions of white matter. These differences are of major importance in contrast discrimination of gray and white matter on the long TR images. Knowing that relaxation values and spin densities calculated from routine imaging sequences are in fact reproducible, these normal ranges can now be used to investigate changes occurring in disease states.